Analisis perbedaan tingkat pengetahuan dan sikap sebelum dan sesudah penyuluhan HIV/AIDS pada ibu hamil - Nur Rohmah; Neno Fitriyani Hasbie; Nopi Sani; Festy Ladyani Mustofa (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Examinations during pregnancy, such as HIV/AIDS screening, need to be carried out early. The transmission of the disease from mother to child should be a concern during pregnancy, childbirth, and the postpartum period. This transmission can be prevented through early testing of pregnant women. The dominant factors influencing HIV/AIDS screening among pregnant women are their level of knowledge and attitudes. Purpose: To analyze differences in knowledge and attitudes of pregnant women regarding HIV/AIDS counseling at the Wede Ar'rachman Primary Clinic in Bandar Lampung. Method: This was a qualitative study using pre-experimental design and pre- and post-test group approaches. The study population was pregnant women. A sample of 30 respondents was selected using a purposive sampling technique. A questionnaire was used as the instrument. Data Analysis Using the Wilcoxon test. Results: Before the counseling session, 17 respondent (56.7%) had poor knowledge and 16 respondent (53.3%) had poor attitudes. After the counseling session, 24 respondent (80%) had good knowledge and 20 respondent (66.7%) had good attitudes. There was a difference in the level of knowledge of pregnant women regarding HIV/AIDS (p-value 0.000) and HIV/AIDS (p-value <0.05), and there was a difference in the level of attitudes of pregnant women regarding HIV/AIDS (p-value 0.000). Conclusion: There is an influence on the level of knowledge and attitudes of pregnant women regarding HIV/AIDS. It is hoped that all pregnant women will undergo HIV testing, and then clinic staff will provide ongoing education about HIV/AIDS.